A Practical Quantitative Tool Based on the EXCASS System for the Use of Hoek-Brown’s Disturbance Factor in Slope Excavations - Gulseren Dagdelenler; Harun Sonmez (Applied Sciences, 2025)
The disturbance factor (D) in the Hoek–Brown criterion quantifies excavation-induced rock mass disturbance. Although D is conceptually defined as a continuous parameter ranging from 0 to 1, the most recent Hoek–Brown guidelines provide descriptions only for boundary conditions related to slopes and tunnels. In slope excavations, the degree of disturbance is governed not only by the excavation method but also by the thickness of the removed overburden, with its influence becoming particularly significant in deep excavations. In recent years, the concept of a transitional disturbance factor, varying with depth from the excavation surface, has gained increasing attention. To address this need, the EXCASS system, an empirical method for selecting appropriate excavation techniques based on the Geological Strength Index (GSI) and point load strength (Is50) values, was integrated into the transitional disturbance factor framework in this study. EXCASS allows for the selection of stronger or weaker excavation methods, offering flexibility to control the degree of disturbance induced in the rock mass. Moreover, the disturbance factor at the excavation surface was determined by incorporating both the operational excavation power index and the thickness of the removed overburden. This integrated approach enables a more realistic evaluation of excavation-induced damage in slope stability analyses.